Migration Attitudes of Postgraduate Students: on the Issue of Educational Migration - Maria M. Smyslova (Lomonosov Moscow State University, 2024)
Background. To date, a significant number of researchers have noted the shortage of highly qualified scientific personnel employed in research organizations. It is due to a number of reasons, among which emigration of scientists to those countries where highly qualified work is paid higher can be marked. In this regard, issues related to the international mobility of postgraduate students, including educational mobility, are very important. Objective. The study focuses on the socio-psychological characteristics of postgraduate students' attitudes to educational migration. Study Participants. The study involved students of postgraduate schools at research organizations involved in the training of graduate students in the field of educational sciences, as well as pedagogical universities in Moscow, St. Petersburg, and other regions of the Russian Federation. A total of 803 respondents were interviewed. Methods. The article is based on the materials of a monitoring questionnaire. Results. The study revealed a connection between socio-demographic factors (gender, age) and attitudes related to educational migration: men more often indicate a desire to improve their professional qualifications abroad; with age, the number of graduate students wishing to study abroad decreases. In addition, the influence of socio-stratification factors (the income level of graduate students and the educational status of the family) on attitudes towards educational migration was revealed: high-income graduate students, as well as those graduate students whose parents have academic degrees, are more focused on professional development abroad. The study also showed that migration attitudes related to temporary educational migration are significantly more widespread among graduate students than among researchers. Conclusion. The attitudes of graduate students related to educational migration are determined by the influence of a number of socio-demographic and socio-stratification factors. At the same time, studying abroad is considered as a career elevator, primarily by those postgraduate students who do not plan to link their further professional activities with scientific work and teaching at budgetary institutions. Also, the larger migration mobility has been revealed in postgraduate students as a socio-professional group in comparison with researchers.